The Psychosocial and Emotional Experience of Breastfeeding - Marie Dietrich Leurer; Eunice Misskey (SAGE Publishing, 2015)
Breastfeeding is acknowledged as optimal infant nutrition, yet despite high initiation rates, early cessation remains common. To understand why, we asked mothers in Western Canada how they felt about their breastfeeding experience. A total of 191 women (response rate 35%) responded to a survey distributed by public health nurses. While many women felt positive about their overall breastfeeding experience, others shared mixed or negative emotions. Several themes were evident: (a) Most women reported a variety of positive aspects beyond the health benefits, (b) lactation difficulties were commonly reported, and (c) diversity among the reflections highlights the uniqueness of each breastfeeding journey. The findings reaffirm the need for breastfeeding programs to holistically promote the range of positive aspects while providing realistic information on common challenges and strategies to overcome these. Mothers require individualized support that assesses psychosocial and emotional needs and offers encouragement, reassurance, and acknowledgment of the range of experiences.